The Foreign Relations of Elizabeth I
XVII, 231 p.
Keywords: This edited volume brings together a collection of provocative essays examining a number of different facets of Elizabethan foreign affairs, encompassing England and The British Isles, Europe, and the dynamic civilization of Islam. As an entirely domestic queen who never physically left her realm, Elizabeth I cast an inordinately wide shadow in the world around her. The essays is this volume collectively reveal a queen and her kingdom much more connected and integrated into a much wider world than usually discussed in conventional studies of Elizabethan foreign affairs.